Terrible tsarinas : five Russian women in power - Troyat, Henri, 1911-2007 (Algora Pub., 2001)
Five flamboyant, "full-blooded" women had a chance to rule Russia. How did it happen, and how did they do? In today's debates about male-female parity, much goes unsaid. Troyat's book brings back the past, when women really had political power. A realisti